1959
DOI: 10.2134/agronj1959.00021962005100060001x
|View full text |Cite
|
Sign up to set email alerts
|

Salt Resistance of Protoplasm as a Test for the Salt Tolerance of Agricultural Plants1

Abstract: Synopsis The protoplasmic salt resistance of plants as measured by the effect of NaCl upon the vacuole and cytoplasm was found to be in agreement with field results and leaf succulence determinations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

1961
1961
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…Our results suggest that barley is the most tolerant to salinity at the seedling and young plant stages and that wheat, gram and mustard are moderately tolerant. In general, salt tolerance seems to depend on how high a salt concentration can be tolerated by the protoplasm without injury (Repp et al 1959), and plants with low tolerance suffer in saline soil because of injury to the protoplasm from salt accumulation, rather than from desiccation (Kramer 1983). Under saline conditions, the effects of ions on the absorption of other ions are also of particular interest.…”
Section: Discussionmentioning
confidence: 99%
“…Our results suggest that barley is the most tolerant to salinity at the seedling and young plant stages and that wheat, gram and mustard are moderately tolerant. In general, salt tolerance seems to depend on how high a salt concentration can be tolerated by the protoplasm without injury (Repp et al 1959), and plants with low tolerance suffer in saline soil because of injury to the protoplasm from salt accumulation, rather than from desiccation (Kramer 1983). Under saline conditions, the effects of ions on the absorption of other ions are also of particular interest.…”
Section: Discussionmentioning
confidence: 99%
“…We agree that Ca is essential in maintaining the structural and functional integrity of membranes, but the effects observed with barley roots seem to be primarily osmotic. Shapovalov (19) (17) found that osmotic potentials between -14 and -18 bars (0.3 and 0.4 molal NaCl) killed 50%o of the cells of many cultivated plants. On the other hand, the lower internal OP and greater resistance of nonvacuolated tissues to osmotic shock have been documented before.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, several techniques have been proposed. Resistance to osmotic shock (46), reaction to dye reduc tion techniques (52), cyclosis and plasmolysis (43), respiration rate, solute uptake (41), rooting, and survival have all been proposed as possible criteria for selecting salt tolerant lines. As yet, none of these methods has proven wholly reliable or been widely accepted.…”
Section: Discussionmentioning
confidence: 99%